Algorithm for Public Electric Transport Schedule Control for Intelligent Embedded Devices - Alps, Ivars; Potapov, Andrey; Gorobetz, Mikhail; Levchenkov, Anatoly (Electrical, Control and Communication Engineering, 2010)
In this paper authors present heuristics algorithm for precise schedule fulfilment in city traffic conditions taking in account traffic lights. The algorithm is proposed for programmable controller. PLC is proposed to be installed in electric vehicle to control its motion speed and signals of traffic lights. Algorithm is tested using real controller connected to virtual devices and real functional models of real tram devices. Results of experiments show high precision of public transport schedule fulfilment using proposed algorithm.